Influence of dynamic stretching on ankle joint stiffness, vertical stiffness and running economy during treadmill running - Pamboris, George M.; Noorkoiv, Marika; Baltzopoulos, Vasilios; Powell, Douglas W.; Howes, Tom; Mohagheghi, Amir A. (Frontiers in Physiology, 2022)
The purpose of the present study was to investigate whether and how dynamic stretching may influence running economy. A crossover design with a minimum of 48 h between experimental (dynamic stretching) and control conditions was used. Twelve recreational runners performed a step-wise incremental protocol to the limit of tolerance on a motorised instrumented treadmill. The initial speed was 2.3 m/s, followed by increments of 0.2 m/s every 3 min. Dynamic joint stiffness, vertical stiffness and running kinematics during the initial stage of the protocol were calculated. Running economy was evaluated using online gas-analysis. For each participant, the minimum number of stages completed before peak O2 uptake (V̇O2peak) common to the two testing conditions was used to calculate the gradient of a linear regression line between V̇O2 (y-axis) and speed (x-axis). The number of stages, which ranged between 4 and 8, used to construct individual subject regression equations. Non-clinical forms of magnitude-based inference were used to assess outcomes. The dynamic stretching protocol resulted in a possible decrease in dynamic ankle joint stiffness (-10.7%; 90% confidence limits ±16.1%), a possible decrease in vertical stiffness (-2.3%, ±4.3), a possibly beneficial effect on running economy (-4.0%, ±8.3), and very likely decrease in medial gastrocnemius muscle activation (-27.1%, ±39.2). The results indicate that dynamic stretching improves running economy, possibly via decreases in dynamic joint and vertical stiffness and muscle activation. Together, these results imply that dynamic stretching should be recommended as part of a warm-up.